Bank diversity and SME innovation: evidence from China. Issue 2 (28th October 2019) - Li, Hongyu; Wu, Junjie; Lu, Zhiqiang
Abstract : Purpose: The purpose of this paper is to examine the relationship between bank diversity and small- and medium-sized enterprise (SME) firm innovation in China to evaluate the impact of recent bank deregulation. Design/methodology/approach: Using a large data set that includes 8, 143 firm-year observations of 1, 122 listed SME firms in China and baseline and robustness regression analyses, the authors identify how bank diversity affects firm innovation and via what economic mechanisms. Potential endogeneity problems are considered and addressed in the design and analysis to minimize research bias. Findings: The authors find robust evidence that bank diversity improves firm innovation. Specifically, the findings suggest that the positive effects of bank diversity on firm innovation are only significant for the firms which are more external finance dependent, have fewer growth opportunities and/or located in the provinces having low financial market development. Originality/value: This study provides novel evidence and insights into the relationship between banking market structure and the determinants of firm innovation in the Chinese context, as a result of China's banking deregulation.